You are here:

# Algebra/Algebra 1

Question
Solve the system by substitution

2x-4y=8
-3x=9y=-18

Since we have 2x - 4y = 8, we can add 4y to both sides.  This gives 2x = 8 + 4y.
Dividing the entire equation by 2 gives x = 4 + 2y.

I believe the 2nd equation is suppose to really be -3x - 9y = -18.

Multiplying the entire equation by -1 gives 3x + 9y = 18.
Since x = 4 + 2y, we can multiply by 3 and get 3x = 12 + 6y.

Putting 3x = 12 + 6y into 3x + 9y = 18 gives 12 + 6y + 9y = 18.
Since 6+9 is 15, we have a 15y on the left side.
Subtracting 12 from both sides leaves a 6 on the right.
This gives 15y = 6.

Dividing both sides by 15 gives y = 6/15 = 2/5.
Putting that in the 1st equation gives 2x - 4(2/5) = 8.
Since 4(2/5) = 8/5, and 8 = 40/5, we can add 8/5 to both sides.
This gives 2x = 48/5.
Dividing by 2 on both sides gives x = 24/5.

Putting x = 24/5 and y = 2/5 into -3x - 9y gives -72/5 - 18/5 = -90/5.
Dividing -90 by 5 gives -18, which is what's there, so that has been done correctly.

Algebra

Volunteer

#### Scott A Wilson

##### Expertise

Any algebraic question you've got. That includes question that are linear, quadratic, exponential, etc.

##### Experience

I have solved story problems, linear equations, parabolic equations. I have also solved some 3rd order equations and equations with multiple variables.

Publications
Documents at Boeing in assistance on the manufacturiing floor.

Education/Credentials
MS at math OSU in mathematics at OSU, 1986. BS at OSU in mathematical sciences (math, statistics, computer science), 1984.

Awards and Honors
Both my BS and MS degrees were given with honors.

Past/Present Clients
Students in a wide variety of areas since the 80's; over 1,000 of them have been in algebra.